TABAQUISMO PARENTAL Y RIESGO DE LEUCEMIA LINFOBLÁSTICA AGUDA INFANTIL EN SOLCA GUAYAQUIL, ECUADOR - LUDEÑA ORDOÑEZ, VICENTE AUGUSTO (2024)
Acute lymphoblastic leukemia (ALL) is a malignant neoplasm related to blood, it has a high incidence in Ecuador, but its origin remains not completely clarified. Previous studies have found that cigarette smoke contains several chemicals that damage pluripotent hematopoietic stem cells and myeloid cells, but their impact on the lymphoid lineage is unknown. Also considering the scarcity of updated evidence, and its contradictory nature, it was necessary to design the present case-control study with the objective of determining the influence of parental smoking on the development of ALL. The 103 selected cases corresponded to a sample of children diagnosed with ALL who attended with their biological parents for a control consultation at SOLCA-Guayaquil, while the 103 controls were randomly selected from children without ALL treated at the outpatient clinic of IESS Ceibos. Two sources were used to collect data: 1) the medical history and 2) a smoking history questionnaire. To determine the association between parental smoking and childhood ALL Fisher's exact test or Chi-Square was used, and the odds ratio was estimated by means of multivariate logistic regression. Based on the findings of the logistic regression, its concluded that paternal smoking before and during conception increases the risk of ALL (1.9 and 3.1 times, respectively). Furthermore, dependent maternal smoking also increases the risk of ALL by 2.7 times if it occurs after birth. Therefore, the importance of avoiding maternal and paternal smoking before, during and after conception should be promoted.